2013
DOI: 10.1016/j.envpol.2013.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and accumulation of four PPCP/EDCs in two leafy vegetables

Abstract: Many pharmaceutical and personal care products (PPCPs) and endocrine-disrupting chemicals (EDCs) are present in reclaimed water, leading to concerns of human health risks from the consumption of food crops irrigated with reclaimed water. This study evaluated the potential for plant uptake and accumulation of four commonly occurring PPCP/EDCs, i.e., bisphenol A (BPA), diclofenac sodium (DCL), naproxen (NPX), and 4-nonylphenol (NP), by lettuce (Lactuca sativa) and collards (Brassica oleracea) in hydroponic cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(96 citation statements)
references
References 38 publications
8
86
0
2
Order By: Relevance
“…Ignoring the instability issue, the total mass uptake ranged from 0.002% (tomatoes) to 0.02% (lettuce, BPA) and 0.07% (lettuce, NP) of the total amount of both contaminants applied to both crops, with roots containing the highest concentrations of each. These results support those of Dodgen et al [36], who also reported maximum accumulation of BPA and NP in roots of lettuce and collards grown hydroponically, with minimal transport into aerial portions of the plants. These results indicate that uptake of both compounds by the plants is more efficient with foliar exposures, relative to root-only exposures.…”
Section: Discussionsupporting
confidence: 92%
“…Ignoring the instability issue, the total mass uptake ranged from 0.002% (tomatoes) to 0.02% (lettuce, BPA) and 0.07% (lettuce, NP) of the total amount of both contaminants applied to both crops, with roots containing the highest concentrations of each. These results support those of Dodgen et al [36], who also reported maximum accumulation of BPA and NP in roots of lettuce and collards grown hydroponically, with minimal transport into aerial portions of the plants. These results indicate that uptake of both compounds by the plants is more efficient with foliar exposures, relative to root-only exposures.…”
Section: Discussionsupporting
confidence: 92%
“…Estimated uptake by plants (Equations 5 -7) suggest that while only 4 % of the bioavailable BPA could enter the soil pore water, which is readily taken up into various food crops (Figure 4a) with leafy vegetables being particularly susceptible to BPA accumulation, followed by root vegetables and cereal grains. Uptake of BPA has been demonstrated in lettuce and brassicas in the laboratory using hydroponic systems which likely over-estimate uptake compared to that likely to occur in soil cultivation where only a small proportion of the BPA is predicted to be present in the pore 23 water and is available for plant uptake [Dodgen et al, 2013]. However, it must be noted that uptake into crops is different from subsequent human exposure as the latter is dependent on the amount of the crops consumed.…”
Section: Equilibrium Partitioning Modelingmentioning
confidence: 99%
“…Because of the ubiquitous presence of BPA in water systems and the potential use of reclaimed water for irrigation to mediate water shortages, interest in determining whether BPA accumulates in food crops has been increasing (Liao and Kannan, 2013;Mezcua et al, 2012). The concentrations of BPA in lettuce and collard tissue have been reported to reach 23 ng/kg and 331 ng/kg, respectively (Dodgen et al, 2013). However, limited information is available on the degradation of BPA by these edible fungi.…”
Section: Introductionmentioning
confidence: 98%